Engine of modernity The omnibus and urban culture in nineteenth-century Paris - Belenky, Masha (Manchester University Press, 2020)
"Engine of Modernity: The Omnibus and Urban Culture in Nineteenth-Century Paris" examines the connection between public transportation and popular culture in nineteenth-century Paris through a focus on the omnibus - a horse-drawn vehicle for mass urban transport which enabled contact across lines of class and gender. A major advancement in urban locomotion, the omnibus generated innovations in social practices by compelling passengers of diverse backgrounds to interact within the vehicle's close confines. Although the omnibus itself did not actually have an engine, its arrival on the streets of Paris and in the pages of popular literature acted as a motor for a fundamental cultural shift in how people thought about the city, its social life, and its artistic representations. At the intersection of literary criticism and cultural history, "Engine of Modernity" argues that for nineteenth-century French writers and artists, the omnibus was much more than a mode of transportation. It became a metaphor through which to explore evolving social dynamics of class and gender, meditate on the meaning of progress and change, and reflect on one's own literary and artistic practices.